The Poetics of Foresight and the Effectiveness of Hidden Discourses: A Reading of Mohamed Imran’s Collection “It’s me who has fore sought” - BAROUK, HICHAME (Milev Journal of Research and Studies, 2015)
The present study investigates the poetics of foresight and the effectiveness of hidden discourses within Mohamed Imran’s poem. Actually, the deep foresight contributes to the integration of some objects such as dream, love and death by dint of different discourses within the modern text, especially the mystical and mythological discourse in accordance with the conscientious poetic ambiguity which transcends the boundaries of the apparent and the superficial. Consequently, this poem provides life with the foresight that enlightens its mysteries, and from which it takes its living elements in order to build its world within a fertile and productive relationship. Building on this ground, we attempt to demystify the poetics of foresight and the extent to which it belongs to the mystical discourse embedded therein through two effects: the effectiveness of dream which is shaped by the prophetic reality, and that of death which is considered by Mohamed Imran as the great bearer in poem writing.